Escape from the Matrix: Multiple Mechanisms for Fibroblast Activation in Pulmonary Fibrosis - Laurent, Geoffrey J. (American Thoracic Society, 2008)
Lung fibrosis is a recognized feature of many chronic lung diseases and is central to the pathogenesis of idiopathic pulmonary fibrosis, a disease that carries a prognosis worse than many cancers. Current research into this condition is defining the key pathways of activation either in resident fibroblasts, matrix-producing cells derived from circulating fibrocytes, or epithelial cells that appear to transdifferentiate to fibroblast-like cells. The downstream signaling pathways are also being delineated as well as the gene interactions leading to altered cell phenotype. These studies have led to an appreciation that multiple pathways, including inflammatory and coagulation cascades, are involved in the pathogenesis of idiopathic pulmonary fibrosis. As these facts come to light, we are exploring promising new approaches to treat fibroses and halt the inexorable progression that is a feature of these disorders. This article reviews these findings and our current concepts of the key molecular events leading to tissue damage and excessive matrix deposition in lung fibrosis. It also highlights the need for new studies to delineate alternative pathogenetic mechanisms and integrate these pathways so we have a framework to better understand their importance in individual patients.